Factors influencing willingness to participate in new drug trial studies: a study among parents whose children were recruited into these trials in northern Ghana. (December 2016) - Akazili, James; Chatio, Samuel; Achana, Fabian; Oduro, Abraham; Kanmiki, Edmund; Baiden, Frank
Abstract Background During the last decade, the number of clinical trials conducted in sub-Saharan Africa has increased significantly which has helped to address priority health problems in the region. Navrongo health research centre since it was established in 1989, has conducted several trial studies including rectal artesunate trial in the Kassena-Nankana districts. However, there is little evidence-based for assessing the impact of new drug trials. This study explored factors that motivate parents to allow their children to participate in new drug trials in northern Ghana. Method The study used both quantitative and qualitative methods. The participants were randomly selected from among parents whose children were enrolled in a new drug trial conducted in the Kassena-Nankana districts between 2000 and 2003. QSR Nvivo 9 software was used to code the qualitative data into themes before analysis while STATA software Version 11.2© was used to analyze the quantitative data. Results The results showed that majority (95.9 %) of the parents were willing to allow their children to be enrolled in future new drug trials. The main factors motivating their willingness to allow their children to be enrolled in these trials were quality of health care services offered to trial participants (92.9 %), detail medical examination (90.8 %), promptness of care provided (94.4 %) and quality of drugs (91.9 %). Other factors mentioned included disease prevention (99.5 %) and improved living standard (96.1 %). Parents reported that the conduct of these trials had reduced the frequency of disease occurrences in the communities because of the quality of health care services provided to the children recruited into these trial studies. Conclusion Though the implementation of clinical trials in the study area is believed to have positive impact on health status of people particularly trial participants, measures should however be taken to address safety and likely side effects of new drugs given to trial participants during these trial studies.